Beyond Political Skin Colonial to National Economies in Indonesia and Vietnam (1910s-1960s) - Thuỷ, Phạm Văn.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book explains the dynamics behind the economic transformation from colonial era to post-independence period in Indonesia and Vietnam. It analyses the different policies of Vietnamese and Indonesian governments towards the economic legacies of colonialism remaining in the countries after independence. It also demonstrates that despite critical differences between the two nation-states, Vietnamese and Indonesian leadership were pursuing similar long-term goals, which is to obtain a truly independent national economy. The book discusses the way in which the Indonesian government attained complete economic control which resembled the socialist transformation of North Vietnam in the 1950s and the various means by which the government of South Vietnam concentrated economic power in its hands during the late 1950s and early 1960s. It also explores how the Indonesian government was determined to get rid of the economic legacy of Dutch colonialism by placing the entire economy under the strong state control and ownership, in accordance with the spirit of Guided Democracy and Guided Economy in the late 1950s and the early 1960s. This book is a point of reference for students, researchers and academics interested in a comparative analysis of the economic systems implemented by the colonial and fascist powers in Indonesia and Vietnam.
Preface and Acknowledgements -- Introduction -- The Subject -- Key Concepts -- Sources and Structure -- 1 Indonesia and Vietnam: Pre-war Economic Conditions -- 1.1 The Colonial Period -- 1.2 Racial Dimension -- 1.3 Economic Structure -- 1.4 Colonial Drain -- 1.5 The Japanese Occupation -- 1.6 Vietnam -- 1.7 Indonesia -- 2 Vietnamese Nationalism and Socialism -- 2.1 The DRV Government -- 2.2 From Nationalism to Communism -- 2.3 Economic Transformation -- 2.4 Diệm's Nationalism -- 3 The Indonesian Struggle for Survival, 1945-1949 -- 3.1 Economic Institutions -- 3.2 The Preferred Economic System -- 3.3 Economic Concessions -- 3.4 Early Economic Transformation -- 3.5 The Return of the Dutch -- 4 The Democratic Experiment, 1950-1957 -- 4.1 The Indonesian Cabinets -- 4.2 Re-formulating the National Economy -- 4.3 Indonesianisasi -- 4.4 Entrenched Dutch Position -- 5 The Guided Economy -- 5.1 The Military-Civil Administration -- 5.2 Ideological Basis of Guided Economy -- 5.3 Take-over and Nationalization -- 5.4 The Business Engagement -- Conclusion -- Appendix -- Bibliography. .
Keywords: Sociology; Economic development; Southeast Asia -- History; Sociological Theory; Development Studies; History of Southeast Asia